1981
DOI: 10.1073/pnas.78.9.5533
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements in the chloroplast genomes of mung bean and pea

Abstract: We have mapped all the cleavage sites for the restriction endonucleases BstEII, Kpn I, Pst I, Pvu H, Sac I, Sal I, Sma I, and Xho I on the circular chloroplast chromosomes from mung bean and pea. The mung bean chloroplast genome measures 150 kilobase pairs (kb) in length; it includes two identical sequences of 23 kb that contain the ribosomal genes and are arranged as an inverted repeat separated by single-copy regions of 21 and 83 kb. The pea chloroplast genome is only 120 kb in size, has only one set of ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(80 citation statements)
references
References 29 publications
0
79
0
1
Order By: Relevance
“…When ctDNA was digested to completion with the restriction enzyme Sail, there were 10 identifiable ctDNA fragments generated, as determined by gel electrophoresis (14). These fragments were as follows: (i) the 44-kbp SalI-A; (ii) the 22.8-kbp SalI-B; (iii) the 16-kbp SalI-C; (iv) the 12.4-kbp SalI-D; (v) the 10.3-kbp SalI-E; (vi) the 10-kbp Sall-F; (vii) the 2.3-kbp Sall-G; and (viii) three fragments of approximately 1 kbp in size, all of which were clustered between the Sall C and Sall A fragments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When ctDNA was digested to completion with the restriction enzyme Sail, there were 10 identifiable ctDNA fragments generated, as determined by gel electrophoresis (14). These fragments were as follows: (i) the 44-kbp SalI-A; (ii) the 22.8-kbp SalI-B; (iii) the 16-kbp SalI-C; (iv) the 12.4-kbp SalI-D; (v) the 10.3-kbp SalI-E; (vi) the 10-kbp Sall-F; (vii) the 2.3-kbp Sall-G; and (viii) three fragments of approximately 1 kbp in size, all of which were clustered between the Sall C and Sall A fragments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Restriction enzyme site mapping across a plethora of plants demonstrated that the cpDNA has a circular plasmidlike structure, with the only significant difference being the number of IR regions (reviewed in Palmer, 1992). Restriction enzyme site mapping has the advantage over EM and reassociation kinetics in that smaller DNA fragments can be analyzed, resulting in less error, and multiple restriction enzymes can be used to map the same molecule (Palmer and Thompson, 1981). A more recently used technique was PFGE of chloroplasts embedded in agarose (Deng et al, 1989;Backert et al, 1995), which eliminated the need to purify cpDNA and reduced shearing.…”
Section: Discussionmentioning
confidence: 99%
“…Pea is a member of the Fabaceae and possesses a smaller chloroplast genome ( ‫ف‬ 120 kb) with only a single copy of the sequence corresponding to the IRs (Palmer and Thompson, 1981). Extended cpDNA fibers of pea were hybridized with both the LSC/SSC probes and the 12.2-kb IR probe.…”
Section: Cpdna Molecules From Pea Showed Less Structural Diversity Thmentioning
confidence: 99%
“…The 32 PssDNA was a 450-nucleotide segment internal to the plastid 16S rRNA gene (Cerutti and Jagendorf, 1991), and the complementary substrate was the 120-kb polyploid chloroplast genome (Palmer and Thompson, 1981;Palmer, 1985). After incubation, the DNA was purified and digested with Pstl, under conditions that minimize branch migration.…”
Section: Strand-transfer Activity In Permeabilized Chloroplastsmentioning
confidence: 99%